2023
DOI: 10.1038/s41419-023-05660-z
|View full text |Cite
|
Sign up to set email alerts
|

RIP3-mediated microglial necroptosis promotes neuroinflammation and neurodegeneration in the early stages of diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a leading cause of blindness that poses significant public health concerns worldwide. Increasing evidence suggests that neuroinflammation plays a key role in the early stages of DR. Microglia, long-lived immune cells in the central nervous system, can become activated in response to pathological insults and contribute to retinal neuroinflammation. However, the molecular mechanisms of microglial activation during the early stages of DR are not fully understood. In this study, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Necrosis can result in cell membrane rupture and cell content release, such as HMGB1, which can be more proinflammatory than apoptosis ( 18 ). On the other hand, RIP3 can induce necroptosis and the production of multiple cytokines, thereby participating in the inflammatory response of related diseases ( 19 ). The mRNA and protein expression levels of HMGB1 and RIP3 were analyzed in TRALI rat lungs to explore the relationship between inflammation and HMGB1/RIP3 in TRALI.…”
Section: Resultsmentioning
confidence: 99%
“…Necrosis can result in cell membrane rupture and cell content release, such as HMGB1, which can be more proinflammatory than apoptosis ( 18 ). On the other hand, RIP3 can induce necroptosis and the production of multiple cytokines, thereby participating in the inflammatory response of related diseases ( 19 ). The mRNA and protein expression levels of HMGB1 and RIP3 were analyzed in TRALI rat lungs to explore the relationship between inflammation and HMGB1/RIP3 in TRALI.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive oxidative stress in the CNS can lead to neuronal damage [ 34 , 35 , [63] , [64] , [65] ]. Interestingly, primarily peripheral redox imbalance can also induce neuroinflammation and nerve damage, resulting in neuropathic pain in diabetes [ 66 , 67 ]. In the present study, we demonstrated that peroxynitrite could be a critical player in disrupting the ratio of Treg/Th17 in the peripheral immune system and aggravating neuroinflammation and neurological deficit in active EAE/MS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The microglia-mediated inflammatory response can be attenuated pharmacologically by drugs such as minocycline [ 117 ]. A recent report showed that microglia undergo necroptosis in DR secondary to hyperglycemia [ 118 ]. In this study, the authors used a pharmacological inhibitor of necroptosis and concluded that inhibiting necroptosis of microglia ameliorated retinal neuroinflammation and neurodegeneration, thereby suggesting a protective role of the microglia.…”
Section: Myeloid Cells In Diabetic Retinopathymentioning
confidence: 99%